2018
DOI: 10.1038/s41524-018-0125-4
|View full text |Cite
|
Sign up to set email alerts
|

Screw dislocation structure and mobility in body centered cubic Fe predicted by a Gaussian Approximation Potential

Abstract: The plastic flow behavior of bcc transition metals up to moderate temperatures is dominated by the thermally activated glide of screw dislocations, which in turn is determined by the atomic-scale screw dislocation core structure and the associated kink-pair nucleation mechanism for glide. Modeling complex plasticity phenomena requires the simulation of many atoms and interacting dislocations and defects. These sizes are beyond the scope of first-principles methods and thus require empirical interatomic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…Once generated, ML potentials enable accurate simulations that are orders of magnitude faster than the reference method. They can solve challenging structural problems, as has been demonstrated for the atomic-scale deposition and growth of amorphous carbon films 13 , for proton-transfer mechanisms 14 or dislocations in materials 15,16 , involving thousands of atoms in the simulation. More recently, it was shown that ML potentials can be suitable tools for global structure searches targeting crystalline phases [17][18][19][20] , clusters [21][22][23][24] , and nanostructures 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Once generated, ML potentials enable accurate simulations that are orders of magnitude faster than the reference method. They can solve challenging structural problems, as has been demonstrated for the atomic-scale deposition and growth of amorphous carbon films 13 , for proton-transfer mechanisms 14 or dislocations in materials 15,16 , involving thousands of atoms in the simulation. More recently, it was shown that ML potentials can be suitable tools for global structure searches targeting crystalline phases [17][18][19][20] , clusters [21][22][23][24] , and nanostructures 25 .…”
Section: Introductionmentioning
confidence: 99%
“…We now briey outline the Gaussian Approximation Potential (GAP) 47 framework, and how we apply it to create a potential energy surface for 3BPA that reproduces quantum mechanical energies to within 1.0 kcal mol À1 root mean square (RMS) error. GAP has been applied to many different materials and compounds, [53][54][55][56][57][58][59][60][61][62][63] and has been described in detail elsewhere, 64,65 and so we summarize here only the main features. Although the probabilistic and linear regression viewpoints are entirely equivalent, we follow the latter here because it is likely to be more familiar, and we will not be making use of the uncertainty estimates and parameter optimization techniques that follow naturally from the former.…”
Section: Creating a Gaussian Approximation Potentialmentioning
confidence: 99%
“…We now briefly outline the Gaussian Approximation Potential (GAP) 46 framework, and how we apply it to create a potential energy surface for 3BPA that reproduces quantum mechanical energies to within 1.0 kcal mol −1 root mean square (RMS) error. GAP has been applied to many different materials and compounds, [52][53][54][55][56][57][58][59][60][61][62] and has been described in detail elsewhere, 63,64 and so we summarize here only the main features. Although the probabilistic and linear regression viewpoints are entirely equivalent, we follow the latter here because it is likely to be more familiar, and we will not be making use of the uncertainty estimates and parameter optimization techniques that follow naturally from the former.…”
Section: Creating a Gaussian Approximation Potentialmentioning
confidence: 99%